1999
DOI: 10.1001/archopht.117.1.84
|View full text |Cite
|
Sign up to set email alerts
|

A New Pressure Attenuation Index to Evaluate Retinal Circulation

Abstract: Background: Low ocular perfusion pressure (two thirds of mean arterial pressure minus intraocular pressure) and myopia have been associated with protection of the retina from clinical diabetic retinopathy. This prompts the question as to whether myopia's protective role could also be a pressure effect, given that pressure could be dissipated in the longer arteriole tree of the myopic eye.Methods: We combined the Ohm, Poiseuille, and Murray laws to derive the following new formulation: the pressure attenuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 21 publications
(25 reference statements)
1
39
0
Order By: Relevance
“…This is also in correlation with blood flow velocity measurements with bidirectional laser Doppler velocimetry and calculated volume flow rates in the human retinal arteries performed by Riva et al [25]. Yet, there are still no direct measurements of pressure drops in human retinal arteries [14], but Quigley et al [24] estimate a pressure drop from the optical disc to the peripheral vessels with diameters of 30-40 m to be around 15 mmHg, which correlates well with our study. Also the pressure distribution shows similarities with the results from Malek et al [15], except that in our study the pressure around the optic disc is higher ( 15.4 mmHg (2050 Pa) compared to 14.8 mmHg).…”
Section: Discussionsupporting
confidence: 92%
“…This is also in correlation with blood flow velocity measurements with bidirectional laser Doppler velocimetry and calculated volume flow rates in the human retinal arteries performed by Riva et al [25]. Yet, there are still no direct measurements of pressure drops in human retinal arteries [14], but Quigley et al [24] estimate a pressure drop from the optical disc to the peripheral vessels with diameters of 30-40 m to be around 15 mmHg, which correlates well with our study. Also the pressure distribution shows similarities with the results from Malek et al [15], except that in our study the pressure around the optic disc is higher ( 15.4 mmHg (2050 Pa) compared to 14.8 mmHg).…”
Section: Discussionsupporting
confidence: 92%
“…The exact definition of the investigation area may slightly vary from author to author. In this work, we consider an annulus with inner and outer radius of 1 and 1.5 optic disk diameters, where for this latter we consider the average value between the mean vertical and horizontal diameter (1.88 and 1.77 mm, respectively Quigley and Cohen 1999). Figure 4 shows that the model predicted O 2 saturation is within the same range as the corresponding measurement for every considered diameter range.…”
Section: Simulation Results In Baseline Conditionsmentioning
confidence: 88%
“…Liu et al (2009) computed pressure drops of 14.6 mmHg between arterial inlet (close to the optic disk) and arterial outlets smaller than 30 microns, and pressure drops in the range of 11-13 mmHg for larger outlets. Quigley and Cohen (1999) , but with a more pronounced spreading of the data. The difference in data spreading could be due to the topology of the vascular network and the portion of the vascular tree used to display the results.…”
Section: Simulation Results In Baseline Conditionsmentioning
confidence: 91%
“…While retinal capillary pressure is likely to play a role, previous studies have also suggested a role for ocular perfusion pressure which incorporates intraocular pressure. In a previous investigation, Quigely and Cohen combined the Ohm, Poiseuille, and Murray laws and found that the myopic arteriolar tree would produce a 16% greater pressure attenuation than that of emmetropic controls with a linear relationship between mean pressure attenuation index and axial length [22]. Since myopia has been shown to be protective against diabetic retinopathy, Quigley and Cohen postulated that the low-end arteriolar pressure in myopic eyes could be protective mechanism against diabetic retinopathy in myopia [23].…”
Section: Discussionmentioning
confidence: 99%